Endoscopic Submucosal Dissection Outcomes for Gastroesophageal Tumors in Low Volume Units: A Multicenter Survey - Najib Azmi, A.; Khor, C.J.L.; Ho, K.Y.; Pittayanon, R.; Rerknimitr, R.; Ratanachu-ek, T.; Koay, D.S.C.; Koh, J.C.; Ho, S.H.; Goh, K.L.; Mahadeva, S. (Hindawi Publishing Corporation, 2016)
Background and Aims. Endoscopic submucosal dissection (ESD) outcomes have traditionally been reported from high volume centers in East Asia. Data from low volume centers in other parts of Asia remain sparse. Methods. A retrospective survey with a structured questionnaire of 5 tertiary centers in 3 countries in South East Asia was conducted. Details of training and clinical outcomes of ESD cases, with follow-up data from these centers, were analyzed. Results. Seven endoscopists from the 5 centers performed a total of 35 cases of ESD in the upper gastrointestinal tract (UGIT) over a 6-year duration. Details of the lesions excised were as follows: median size was 20 mm, morphologically 20 (68.6%) were flat/depressed and 6 (17.1%) were submucosal, and histologically 27 (77.1%) were neoplastic. The median duration of ESD procedures was 105 minutes, with an en-bloc resection rate of 91.4%. There was 1 (2.9%) case of delayed bleeding, but no perforation nor mortality in any of the cases. The recurrence rate after ESD was 5.7%. A prolonged ESD duration was influenced by a larger size of lesion (25 mm, ) but not by factors related to the training experience of endoscopists. Conclusions. ESD in the UGIT is feasible and safe in low volume centers in Asia.